Deformation and Fracture Behaviour of Polymer Materials - Grellmann, Wolfgang; Langer, Beate (Springer International Publishing : Imprint: Springer, 2017)
This book covers the most recent advances in the deformation and fracture behaviour of polymer material. It provides deeper insight into related morphology-property correlations of thermoplastics, elastomers and polymer resins. Each chapter of this book gives a comprehensive review of state-of-the-art methods of materials testing and diagnostics, tailored for plastic pipes, films and adhesive systems as well as elastomeric components and others. The investigation of deformation and fracture behaviour using the experimental methods of fracture mechanics has been the subject of intense research during the last decade. In a systematic manner, modern aspects of fracture mechanics in the industrial application of polymers for bridging basic research and industrial development are illustrated by multifarious examples of innovative materials usage. This book will be of value to scientists, engineers and in polymer materials science.- Resumé vydavatel
Keywords: polymery; polymerní materiály; mechanické vlastnosti materiálů; deformace; mechanika tuhých těles; lomová mechanika; polymers; polymer materials; mechanical properties of materials; deformations (mechanics); solid-state mechanics; fracture mechanics; elektronické knihy; kolektivní monografie; electronic books; collective monographs